2013
DOI: 10.1007/s10103-013-1500-5
|View full text |Cite
|
Sign up to set email alerts
|

Histological and gene expression analysis of the effects of pulsed low-level laser therapy on wound healing of streptozotocin-induced diabetic rats

Abstract: Diabetes mellitus (DM) is associated with poor wound healing. Studies have shown accelerated wound healing following pulsed low-level laser therapy (LLLT) in non-diabetic animals. The present study aims to evaluate the effect of pulsed LLLT on wound healing in streptozotocin-induced diabetic (STZ-D) rats. We divided 48 rats into two groups of non-diabetic and diabetic. Type 1 DM was induced in the diabetic rat group by injections of STZ. Two, full-thickness skin incisions were made on the dorsal region of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 36 publications
3
41
1
2
Order By: Relevance
“…The safety and effectiveness of PBM on wound healing led researchers to investigate the applicability of this treatment for wound healing in in vitro and in vivo diabetic models. Previous research demonstrated that PBM improved diabetic wound healing by accelerating collagen production, enhancing angiogenesis, increasing wound closure rate, and increasing growth factor expression . These results lead to worldwide clinical trials on diabetic wound healing, especially on diabetic foot ulcers …”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The safety and effectiveness of PBM on wound healing led researchers to investigate the applicability of this treatment for wound healing in in vitro and in vivo diabetic models. Previous research demonstrated that PBM improved diabetic wound healing by accelerating collagen production, enhancing angiogenesis, increasing wound closure rate, and increasing growth factor expression . These results lead to worldwide clinical trials on diabetic wound healing, especially on diabetic foot ulcers …”
mentioning
confidence: 91%
“…Previous research demonstrated that PBM improved dia-betic wound healing by accelerating collagen production, 7 enhancing angiogenesis, 8 increasing wound closure rate, [9][10][11] and increasing growth factor expression. 10,12 These results lead to worldwide clinical trials on diabetic wound healing, especially on diabetic foot ulcers. 2,3,13 When proper parameters are established, both laser and light-emitting diode (LED) irradiation improve wound healing implying that the coherence is not essential.…”
mentioning
confidence: 99%
“…19 PW LLLT accelerated the wound-healing process in streptozotocin (STZ)-induced TIDM, as measured by tensiometerical parameters and histological characteristics, and significantly reduced the colony-forming units (CFUs) of bacteria in non-genetic rat models of Types 1 and 2. 13,15,16 In 2016, Ranjbar and Takhtfooladi reported positive effects of CWLLLT (685 nm, 3 J/cm 2 , 5 days) on infected burns with MRSA in TIDM animals. 24 Mesenchymal stem cells (MSCs) release growth factors called secrotomes.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have implicated decreased pro‐inflammatory cytokines (TNF α , IL1 β , IL6), mast cell degranulation, altered MMPs and redox status, decreased cell adhesion complexes as well as modulated bFGF signaling as key players in PBM modulated DM wound healing . There have been specific studies designed to assess the effects of wavelengths, dose, light sources (including OLEDs), pulsing as well as combinations with nutritional supplements such as CoQ10 that have all shown positive correlations .…”
Section: Discussionmentioning
confidence: 99%
“…These studies have implicated decreased pro-inflammatory cytokines (TNFa, IL1b, IL6), mast cell degranulation, altered MMPs and redox status, decreased cell adhesion complexes as well as modulated bFGF signaling as key players in PBM modulated DM wound healing (22)(23)(24)(25)(26)(27). There have been specific studies designed to assess the effects of wavelengths, dose, light sources (including OLEDs), pulsing as well as combinations with nutritional supplements such as CoQ10 that have all shown positive correlations (12,(28)(29)(30)(31)(32)(33)(34)(35)(36). Histological assessment (criteria outlined in Table S2) for re-epithelization and inflammation was performed in each treatment group at day 4 and 10 PBM post-treatments.…”
Section: Discussionmentioning
confidence: 99%